Aplasia cutis congenita with fetus papyraceus: an uncommon case report - Ittigi, Vivekananda; Anto, Aparna (International Journal of Research in Dermatology, 2020)
Aplasia cutis congenita is a condition characterized by congenital absence of all skin layers in a localized or widespread area. Frieden's classification recognized a rare subtype, type V, that is associated with multiple gestations in which there is the in-utero demise of a twin with resultant fetus papyraceus or mummification. A twin pregnancy was complicated by in-utero death of one twin at 5 months. On full term birth of the other twin with fetus papyraceus large defects in the skin of knees were noted bilaterally. Conservative management with topical antibiotics and emollients helped in complete re-epithelialization in few months. As the use of reproductive technologies increase the incidence of multiple gestation and associated conditions are expected to increase. This type is clinically unique in that it is characterized by stellate lesions in a symmetrical distribution over the trunk and extremities, differing from other subtypes, which are typically localized to scalp (70%-85% of cases) or extremities. Management ranges from conservative to surgical grafts.